Vertical Graphene Base Transistor - Mehr, Wolfgang; Dabrowski, Jarek; Lemme, Max C.; Lippert, Gunther; Lupina, Grzegorz; Ostling, Mikael; Xie, Ya-Hong; Scheytt, Christoph ((Refa) FB/IE Zeitschrift für Unternehmensentwicklung und Industrial Engineering)
We present a novel graphene-based-device concept for a high-frequency operation: a hot-electron graphene base transistor (GBT). Simulations show that GBTs have high current on/off ratios and high current gain. Simulations and small-signal models indicate that it potentially allows terahertz operation. Based on energy-band considerations, we propose a specific material solution that is compatible with SiGe process lines.